Branding Riau University as an International Education Destination for Foreign Students - Andrikasmi, Sukamarriko; Indra, Mexsasai; Amir, Yufitriana; Junaidi, Junaidi; Rozi, Fahrur (Universitas Pahlawan Tuanku Tambusai, 2026)
The globalization of higher education has intensified competition, compelling universities to develop strong international brands. Universitas Riau (UNRI), with its strategic location and distinctive Malay cultural identity, possesses significant potential to attract foreign students but currently lacks a structured and integrated branding strategy. This research addresses the problem of UNRI's underdeveloped international brand by analyzing the successful strategies of comparable institutions. The objectives are to (1) analyze the international student recruitment strategies of BINUS University, Universitas Andalas (UNAND), and the Indonesian Institute of the Arts (ISI) Padangpanjang; (2) incorporate stakeholder perspectives from the Malaysian Consulate; and (3) formulate a comprehensive branding model for UNRI. This study employs a qualitative, multi-case design conducted in October 2025. Data were collected through in-depth interviews with key informants and document analysis at each institution. The findings show that successful strategies vary: BINUS emphasizes service excellence and exchange programs, UNAND adopts aggressive scholarship schemes and digital promotion, while ISI Padangpanjang capitalizes on its cultural and arts niche. The Malaysian Consulate highlighted the appeal of Islamic values and scholarship opportunities. The study concludes that UNRI should adopt an “Integrated Niche-Excellence Branding” model by leveraging its unique Malay culture, supported by competitive scholarships, simplified administration, and excellent student services, to position itself as a leading international education destination in ASEAN.